Is There a Reason for the Proton Pump Inhibitor? An Assessment of Prescribing for Residential Care Patients in British Columbia - Chan, Adriel (Can J Hosp Pharm, 2018)
BACKGROUND: The use of proton pump inhibitors (PPIs) may cause significant harm to patients in the residential care setting, as these patients are often frail with multiple morbidities. The extent of non–evidence-based use of PPIs in residential care sites of the Fraser Health Authority in British Columbia is unknown. OBJECTIVE: To determine the proportion of non–evidence-based use of PPI therapy for residential care patients of the Fraser Health Authority. METHODS: This retrospective cross-sectional study was conducted in 6 Fraser Health residential care facilities in British Columbia between April 1, 2015, and March 31, 2016. Two definitions of “evidence-based indications” were used. The first definition encompassed broad evidence-based indications for PPI use, specifically gastroesophageal reflux disease (GERD), peptic ulcer disease (PUD), gastritis, esophagitis, Barrett esophagus, and gastrointestinal protection from concurrent oral steroids, oral nonsteroidal anti-inflammatory drugs, antiplatelet agents, and anticoagulants. The second definition involved common evidence-based indications for PPI use, specifically GERD or PUD. Descriptive statistics were used to evaluate the primary outcome: the proportion of PPI orders without a documented broad or common evidence-based indication for PPI treatment. RESULTS: A total of 331 residential care patients and 407 PPI orders were assessed. The proportion of PPI orders without a documented broad evidence-based indication was 16.2% (66/407). The proportion of PPI orders without a documented common evidence-based indication was 43.7% (178/407). The most frequently documented reason for a PPI order was GERD (214/407 or 52.6%). PPI orders for patients with GERD and gastrointestinal bleeding had the longest duration of therapy during residential care admission, averaging 205.1 and 218.1 days, respectively. CONCLUSION: About 1 in 6 PPI orders for Fraser Health residential care patients did not have a documented broad evidence-based indication, and about 2 in 5 PPI orders did not have a documented common evidence-based indication. These results indicate a need to assess the appropriateness of therapy for every patient with an active PPI order in residential care facilities.